Zeus and Dionysus in the Light of Linear B Records - Duev, Ratko (Fabrizio Serra editore, Pisa - Roma, 2008)
The Greek peoples were not indigenous, but the Greek language arose through the mixture of a group of IE speakers with an earlier population. The theory by P. Kretschmer of their arrival in three successive waves has been rejected. Thus, the first inter-linguistic and intercultural contacts between these IE newcomers and the earlier Balkan and Mediterranean population had begun since the Middle Minoan Ia period (about 2000 B.C., or a little earlier 2100 B.C.). Moreover, the syncretism of IE cults with Balkan and Mediterranean cults began first, maybe between that of Zeus and Dionysus. These contacts and interferences became more intensive in the Mycenaean period when the subjugated Minoan population was absorbed by the conquerors (Mycenaean Greeks), and continued to live in symbiosis with them. However, from the Linear B records we can see that the competition for priority between Zeus and Dionysus, as well as between Di-wi-ja and E-ra, continued in Mycenaean times.